Hypomnemata digitali. Memoria, automatizzazione e controllo sociale - Mutchinick, Joaquin (Mechane, 2020)
Starting from the Platonic concept of hypomnemata, we aim to shed light on the relationship between memory and digital technology. More precisely, we aim to describe, following Stiegler’s hypomnestic retention and Leroi-Gourhan’s exteriorization, how digital technologies shape, store and circulate “collective memories” in modern societies, thus modifying the psychical processes and individuals’ social behaviour. Accordingly, we will schematically outline two crucial aspects of digital hypomnemata’s use: on the one hand, the gradual automatization of an increasingly large amount of individual and collective practices; on the other hand, the increase in social control. In virtue of the notion of “digital governmentality”, shaped by Antoinette Rouvroy and Thomas Berns in the wake of Michel Foucault, we will claim that the interaction between these elements––automatization and social control––leads to a new form of political technology. Last but not least, we will address the challenges surfacing from this new power. relationship.